Кариотип Microtus sosialis и родственные связи видов рода Chionomys и порода Terricola, обитающих в Азербайджане - Мамедрзаева, Е.Т.; Кулиев, Г.Н.; Керимова, З.К.; Кулиев, А.Г.; Шамилов, Э.Н.; Гасымова, Г.Э.; Абдуллаева, А.С. (Фактори експериментальної еволюції організмів, 2015)
Aim. There were studied relational connections of social voles (Microtus socialis) species of genus Chionomys (Ch. roberti, Ch. nivalis, Ch. gud) and species of subgenus Terricola, genus Microtus (M. majori, M. dagestanicus, M. schelkovnikovi). Methods. There were identifi ed common chromosomes of Microtus socialis and species of the genus Chionomys and subgenus Terricola. Results. It was established that in speciation played a role tandem translocations such as telomericcentromeric and telomeric-telomeric fusion of acrocentric chromosomes. Conclusions. The studied species of the genera Chionomys and species of the subgenus Terricola, genus Microtus have the same diploid number and externally similar structure of the karyotype, chromosome sets of these two groups of voles have evolved from common ancestral form of a higher number of chromosomes. Such animals may have had in the karyotype more acrocentric chromosomes similar to karyotype of modern social voles — Microtus socialis. Keywords: Social voles, chromosomes, karyotype, acrocentrics.